Methods of formation of patriotic feelings in youth (Conference Zone, 2022)
Motherland is the holy land where a person is born. By homeland, we mean the motherland, where our parents and descendants shed their navel blood. In order to deeply feel the homeland, it is necessary to know, respect, value and strengthen the examples of patriotism of the people. These feelings, these beautiful high human qualities are a true example of patriotism for our freedom day. That is, the nation is the support of the Motherland.